Effect of internal versus external focus of attention on implicit motor learning in children with developmental coordination disorder. (February 2015) - Jarus, Tal; Ghanouni, Parisa; Abel, Rachel L.; Fomenoff, Shelby L.; Lundberg, Jocelyn; Davidson, Stephanie; Caswell, Sarah; Bickerton, Laura; Zwicker, Jill G.
Highlights: DCD group demonstrated poorer implicit learning in all phases of the study. No differences between focus of attention groups during retention and transfer phase in DCD group. External focus of attention seems to provide advantage to typically developing children but not to children with DCD. Abstract: Children with developmental coordination disorder (DCD) struggle to learn new motor skills. It is unknown whether children with DCD learn motor skills more effectively with an external focus of attention (focusing on impact of movement on the environment) or an internal focus of attention (focusing on one's body movements) during implicit (unconscious) and explicit (conscious) motor learning. Purpose: This paper aims to determine the trends of implicit motor learning in children with DCD, and how focus of attention influences motor learning in children with DCD in comparison with typically developing children. Methods: 25 children, aged 8–12, with ( n  = 12) and without ( n  = 13) DCD were randomly assigned to receive instructions that focused attention externally or internally while completing a computer tracking task during acquisition, retention, and transfer phases. The motor task involved tracking both repeated and random patterns, with the repeated pattern indicative of implicit learning. Results: Children with DCD scored lower on the motor task in all three phases of the study, demonstrating poorer implicit learning. Furthermore, graphical data showed that for the children with DCD, there was no apparent difference between internal and external focus of attention during retention and transfer, while there was an advantage to the external focus of attention group for typically developing children. Conclusion: Children with DCD demonstrate less accuracy than typically developing children in learning a motor task. Also, the effect of focus of attention on motor performance is different in children with DCD versus their typically developing counterparts during the three phases of motor learning. Implications: Results may inform clinicians how to facilitate motor learning in children with DCD by incorporating explicit learning with either internal or external focus of attention within interventions.